Chlorine evolution anode and preparation and application thereof
By using a multi-layer structure intermediate layer and active layer catalytic composition in the chlor-alkali anode, the problem of inactivation of the anode in harsh environments is solved, and higher stability and activity are achieved, and the electrode life is extended.
Patent Information
- Application Number
- CN202510057030.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
The chlor-alkali anode is prone to inactivation in harsh working environments, resulting in a shortened life and affecting actual use.
The chlorine-eliminated anode structure including a matrix, an intermediate layer catalytic composition and an active layer catalytic composition are employed, wherein the intermediate layer catalytic composition comprises iridium oxide, ruthenium oxide and valve metal oxide, the active layer catalytic composition comprises ruthenium oxide, iridium oxide and valve metal oxide, and a multilayer structure is formed by heat treatment.
It significantly improves the stability and activity of the anode, extends the service life of the electrode, and ensures excellent stability and low chlorine potential after long-term operation.
Smart Images

Figure CN119876995A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode preparation used as an anode in an electrolytic cell, and in particular relates to a chlorine evolution anode and preparation and application thereof. Background Art
[0002] The chlor-alkali industry refers to the industry that produces chlorine, hydrogen, caustic soda and other products by electrolyzing saturated brine solutions and uses them as raw materials to produce related chemical products. The commonly used dimensionally stable anode (DSA) is the chlor-alkali anode material, which is generally a binary oxide coated anode containing ruthenium. The anode material has high catalytic activity and has a low chlorine evolution potential during operation. However, due to the harsh working environment of the chlor-alkali anode, the anode will be deactivated during operation, resulting in a loss of anode life, which greatly affects its actual use.
[0003] During the long-term operation of the electrolytic cell, the main reasons that affect the life of the anode are as follows: First, a non-conductive oxide film will be generated on the titanium substrate, which will passivate the titanium substrate, increase the anode potential, and cause the electrode to deactivate; second, during the operation, the active components are easily converted into oxides of other valence states and enter the solution, causing the electrochemical dissolution of the active components of the electrode and causing electrode failure; third, due to the lack of preparation methods, the active coating in the electrode will not be firmly bonded to the titanium substrate, causing the coating to fall off, or the electrode will generate a large number of bubbles during the electrolysis process. The stress generated by the diffusion of bubbles will directly act on the electrode surface, causing the coating to fall off, the electrochemical active sites to decrease, the electrocatalytic performance to decrease, and the electrode to gradually deactivate.
[0004] Therefore, there is an urgent need to develop electrodes containing catalyst coatings with higher stability and activity. Summary of the invention
[0005] In order to improve the above technical problems, the present invention provides a chlorine evolution anode, which comprises a substrate, and the surface of the substrate is coated with an intermediate layer catalytic composition and an active layer catalytic composition in sequence;
[0006] The intermediate layer catalytic composition comprises one or both of iridium oxide and ruthenium oxide and at least one oxide of a valve metal;
[0007] The active layer catalytic composition comprises one or more of ruthenium oxide, iridium oxide and at least one valve metal oxide.
[0008] According to an embodiment of the present invention, the valve metal in the intermediate layer catalytic composition is different from the valve metal in the active layer catalytic composition.
[0009] According to an embodiment of the present invention, the valve metal is selected from at least one of tantalum, titanium, niobium, tin and antimony.
[0010] According to an embodiment of the present invention, in the intermediate layer catalytic composition, the valve metal is selected from at least one of tantalum, titanium and niobium.
[0011] According to an embodiment of the present invention, in the active layer catalytic composition, the valve metal is selected from at least one of titanium, tin and antimony.
[0012] According to an embodiment of the present invention, the intermediate layer catalytic composition may be coated with one or more layers on the surface of the substrate.
[0013] According to an embodiment of the present invention, on the intermediate layer, the active layer catalytic composition may be coated with one or more layers.
[0014] According to an embodiment of the present invention, the intermediate layer catalytic composition is coated on the substrate surface in the form of a solution, that is, the intermediate layer catalytic composition solution is coated on the substrate surface.
[0015] According to an embodiment of the present invention, the solvent used in the intermediate layer catalytic composition solution is at least one of isopropanol and n-butanol; for example, a mixture of isopropanol and n-butanol. Preferably, the volume ratio of isopropanol to n-butanol is 0.1 to 10:1, preferably 1 to 10:1.
[0016] According to an embodiment of the present invention, the method for preparing the intermediate layer catalytic composition solution is:
[0017] Chloroiridic acid hexahydrate (H 2 IrCl 6 6H 2 O), ruthenium trichloride (RuCl 3 ) are mixed with a compound containing a valve metal to obtain the intermediate layer catalytic composition solution.
[0018] According to an embodiment of the present invention, in the preparation of the intermediate layer catalytic composition solution, the compound containing the valve metal is selected from tantalum pentachloride (TaCl 5 ), tetrabutyl titanate (Ti(OC 4 H 9 ) 4 ), niobium pentachloride (NbCl 5 )
[0019] Furthermore, in the intermediate layer catalytic composition solution, the concentration of iridium and / or ruthenium is 0.01-0.3 mol / L, preferably 0.01-0.2 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L.
[0020] Furthermore, in the intermediate layer catalyst composition solution, the concentration of the valve metal is 0.01-0.1 mol / L, preferably 0.01-0.05 mol / L, for example, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L or 0.05 mol / L.
[0021] According to an embodiment of the present invention, the active layer catalytic composition is coated on the surface of the intermediate layer in the form of a solution, that is, the active layer catalytic composition solution is coated on the surface of the intermediate layer.
[0022] According to an embodiment of the present invention, the solvent used in the active layer catalyst composition solution is at least one of isopropanol and n-butanol; for example, a mixture of isopropanol and n-butanol. Preferably, the volume ratio of isopropanol to n-butanol is 0.1 to 10:1, preferably 1 to 10:1.
[0023] According to an embodiment of the present invention, the method for preparing the active layer catalytic composition solution is:
[0024] Chloroiridic acid hexahydrate (H 2 IrCl 6 6H 2 O), ruthenium trichloride (RuCl 3 ) are mixed with a compound containing a valve metal and hydrochloric acid to obtain the active layer catalytic composition solution.
[0025] According to an embodiment of the present invention, in the preparation of the active layer catalyst composition solution, the compound containing valve metal is selected from tetrabutyl titanate (Ti(OC 4 H 9 ) 4 ), tin tetrachloride (SnCl 4 ), antimony trichloride (SbCl 3 )
[0026] Furthermore, in the active layer catalyst composition solution, the concentration of iridium and / or ruthenium is 0.01mol / L to 0.3mol / L, preferably 0.01mol / L to 0.2mol / L, for example, 0.01mol / L, 0.05mol / L, 0.08mol / L, 0.1mol / L, 0.15mol / L, 0.18mol / L, 0.2mol / L;
[0027] Furthermore, in the active layer catalyst composition solution, the concentration of the valve metal is 0.01 mol / L to 0.4 mol / L, preferably 0.01 mol / L to 0.2 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L;
[0028] Furthermore, the content of hydrochloric acid in the active layer catalyst composition solution is 0.015 mL HCl / mL~0.025mL HCl / mL.
[0029] According to an embodiment of the present invention, the substrate is, for example, a titanium substrate.
[0030] The present invention also provides a method for preparing the above-mentioned chlorine evolution anode, the method comprising:
[0031] (S1) coating the intermediate layer catalytic composition on a substrate, heating and heat treating the substrate to obtain a substrate containing the intermediate layer;
[0032] (S2) coating the active layer catalytic composition on the intermediate layer of step (S1), heating and heat treatment, to obtain a substrate containing the active layer and the intermediate layer in sequence;
[0033] (S3) heat-treating the substrate containing the active layer and the intermediate layer in step (S2) to obtain the chlorine evolution anode.
[0034] According to an embodiment of the present invention, before implementing step (S1), the substrate may be pretreated, wherein the pretreatment includes sandblasting, pickling, heating, water washing and drying the substrate to obtain a pretreated titanium substrate.
[0035] Preferably, the sandblasting is performed by using brown corundum sandblasting; for example, using brown corundum sandblasting with a mesh size of 20 to 50.
[0036] Preferably, the pickling is performed by washing with an oxalic acid solution, for example, washing with an oxalic acid solution having a mass concentration of 10% to 20%.
[0037] Preferably, the heating temperature is 90-120° C., and the heating time is 30 to 120 min.
[0038] According to an embodiment of the present invention, in step (S1), the atmosphere of the heat treatment is an oxygen-containing atmosphere, such as a mixed atmosphere of nitrogen and oxygen, such as air.
[0039] According to an embodiment of the present invention, in step (S1), the temperature of the heat treatment is 450 to 550° C., and the time of the heat treatment is 10 to 20 minutes.
[0040] According to an embodiment of the present invention, in step (S2), the atmosphere of the heat treatment is an oxygen-containing atmosphere, such as a mixed atmosphere of nitrogen and oxygen, such as air.
[0041] According to an embodiment of the present invention, in step (S2), the temperature of the heat treatment is 450 to 550° C., and the time of the heat treatment is 10 to 20 minutes.
[0042] According to an embodiment of the present invention, in step (S1), the intermediate layer catalytic composition may be coated multiple times to form a multi-layer intermediate layer.
[0043] According to an embodiment of the present invention, in step (S2), the active layer catalytic composition may be coated multiple times to form a multi-layer active layer.
[0044] According to an embodiment of the present invention, in step (S3), the atmosphere of the heat treatment is an oxygen-containing atmosphere, such as a mixed atmosphere of nitrogen and oxygen, such as air.
[0045] According to an embodiment of the present invention, in step (S3), the temperature of the heat treatment is 450 to 550° C., and the time of the heat treatment is 30 to 60 minutes.
[0046] As an exemplary embodiment of the present invention, the method for preparing the chlorine-evolving anode comprises the following steps:
[0047] (1) Pretreatment of titanium substrate:
[0048] The titanium substrate is sandblasted with 20-50 mesh brown corundum and then rinsed with water; the sandblasted titanium substrate is immersed in an oxalic acid solution with a mass concentration of 10% to 20%, heated to boiling and maintained for 30 to 120 minutes, the pickled titanium substrate is washed with water, and naturally dried to obtain a pretreated titanium substrate;
[0049] (2) coating the intermediate layer catalytic composition solution on the pretreated titanium substrate, and heat treating it in an air atmosphere at a temperature of 450 to 550° C. for 10 to 20 minutes to form an intermediate layer on the surface of the titanium substrate; preferably, the above process can be repeated multiple times to apply multiple coatings;
[0050] (3) coating the active layer catalytic composition solution on the intermediate layer, and performing heat treatment in an air atmosphere at a temperature of 450 to 550° C. for 10 to 20 minutes; preferably, the above process can be repeated multiple times to apply multiple coatings;
[0051] (4) After the coating in step (3) is completed, heat treatment is performed in an air atmosphere at a temperature of 450° C. to 550° C. for a time of 30 minutes to 60 minutes to obtain the chlorine evolution anode.
[0052] Furthermore, in step (2), the loading amount of iridium and / or ruthenium in the chlorine evolution anode is 0.1 g / cm 2 ~1.0g / cm 2 ;
[0053] Furthermore, in step (3), the loading amount of iridium and / or ruthenium in the chlorine evolution anode is 4 g / cm 2 ~10g / cm 2 ;
[0054] The present invention also provides application of the chlorine evolution anode in the chlor-alkali industry.
[0055] Beneficial effects of the present invention:
[0056] The chlorine-analyzing anode of the present invention has an intermediate layer and an active layer. Compared with an electrode without an intermediate layer, its enhanced life can be increased by more than 100 times, and the chlorine-analyzing anode still has excellent stability after long-term operation. This is because the intermediate layer can effectively protect the titanium substrate, preventing the titanium substrate from generating a non-conductive oxide film and causing electrode passivation failure; at the same time, it can enhance the combination of the active layer and the substrate, prevent the catalytic active components from dissolving and falling off, thereby avoiding the deactivation of the anode material, enhancing the operation stability of the anode, and extending the electrode life. The chlorine-analyzing electrode is applied to the chlor-alkali industry, and the chlorine-analyzing anode can obtain a lower chlorine-analyzing potential, better operation stability, and a longer electrode service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is the X-ray diffraction (XRD) pattern corresponding to each catalytic coating of the chlor-alkali anode in Example 5.
[0058] Figure 2 It is a voltage-time curve diagram of the chlorine evolution anode enhanced life test of Example 5 and Comparative Example 2.
[0059] Figure 3 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0060] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0061] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0062] Example 1
[0063] (1) A titanium substrate of 2 cm × 1 cm size was sandblasted with brown corundum, and the residue was cleaned with a compressed air jet. Then, the titanium substrate was immersed in oxalic acid with a mass concentration of 15% at about 120° C. for acid treatment for 1 hour. After the acid treatment, it was ultrasonically cleaned with deionized water and dried naturally to obtain a pretreated titanium substrate.
[0064] (2) preparing an intermediate layer catalyst solution (i.e., an intermediate layer catalyst composition solution), 2 Ir 6 6H 2 O、NbCl 5 Dissolved in isopropanol, where the concentration of Ir is 0.015 mol / L and the concentration of Nb is 0.010 mol / L.
[0065] (3) Prepare an active layer catalyst solution (i.e., an active layer catalyst composition solution), and add RuCl 3 、Ti(OC 4 H 9 ) 4 Dissolved in isopropanol and hydrochloric acid, where the concentration of Ru is 0.3 mol / L, the concentration of Ti is 0.050 mol / L, and the hydrochloric acid is 0.3 mol / L.
[0066] (4) The intermediate layer catalyst solution is evenly coated on the pretreated titanium substrate, dried under an infrared lamp, and then moved to a muffle furnace for thermal oxidation treatment for 15 minutes at a thermal oxidation temperature of 470° C. The above steps are repeated twice;
[0067] (5) The active layer catalyst solution is evenly coated on the pretreated titanium substrate, dried under an infrared lamp, and then moved to a muffle furnace for thermal oxidation treatment for 15 minutes at a thermal oxidation temperature of 470° C. The above steps are repeated 5 times;
[0068] (6) After the last drying, keep the mixture in a muffle furnace for 1 hour at a temperature of 470°C, then take it out and cool it naturally to room temperature to obtain a mixed coating chlorine evolution anode. Sample number #1.
[0069] Example 2
[0070] The chlorine-evolving anode was prepared according to the method of Example 1, except that step (4) was performed only once. The sample number was #2.
[0071] Example 3
[0072] The chlorine-evolving anode was prepared according to the method of Example 1, except that the solvents used in step (2) were isopropanol and n-butanol, and the volume ratio of isopropanol to n-butanol was 1:1. The sample number was #3.
[0073] Example 4
[0074] The chlorine-evolving anode was prepared according to the method of Example 1, except that the solvents used in step (3) were isopropanol and n-butanol, and the volume ratio of isopropanol to n-butanol was 1:1. The sample number was #4.
[0075] Example 5
[0076] The chlorine evolution anode was prepared according to the method of Example 1, except that the concentration of Ir in the intermediate layer catalyst solution in step (2) was 0.030 mol / L. The sample number was #5.
[0077] Figure 1 The X-ray diffraction (XRD) patterns of the catalytic coatings of the chlor-alkali anode of Example 5 are shown in Table 1. The characteristic diffraction peaks of Ti in the intermediate layer catalytic composition are 2θ=35.1°, 38.4°, and 40.2°, corresponding to the (101), (002), and (101) crystal planes, respectively. The active layer catalytic composition and #5 both have RuO 2 Characteristic diffraction peaks 2θ=28.0°, 35.1°, and 54.2°, corresponding to (110), (101), and (211) crystal planes, respectively, indicating the presence of RuO 2 Crystal formation.
[0078] Example 6
[0079] The chlorine evolution anode was prepared according to the method of Example 1, except that the concentration of Ru in the active layer catalyst solution in step (3) was 0.01 mol / L. The sample number was #6.
[0080] Example 7
[0081] The chlorine evolution anode was prepared according to the method of Example 1, except that the concentration of Ru in the active layer catalyst solution in step (3) was 0.05 mol / L. The sample number was #7.
[0082] Example 8
[0083] The chlorine-evolving anode was prepared according to the method of Example 1, except that in step (3), RuCl 3 SnCl 4 As active layer catalyst, the concentration of Ru is 0.03 mol / L, and the concentration of Sn is 0.05 mol / L. The sample number is #8.
[0084] Example 9
[0085] The chlorine evolution anode was prepared according to the method of Example 1, except that in step (2), H 2 Ir 6 6H 2 O、RuCl 3 、TaCl 5As the intermediate layer catalyst, the concentration of Ir is 0.01 mol / L, the concentration of Ru is 0.02 mol / L, and the concentration of Ta is 0.01 mol / L. The sample number is #9.
[0086] Comparative Example 1
[0087] (1) A titanium substrate of 2 cm × 1 cm size was sandblasted with brown corundum, and the residue was cleaned with a compressed air jet. Then, the titanium substrate was immersed in oxalic acid with a mass concentration of 15% at about 120° C. for acid treatment for 1 hour. After the acid treatment, it was ultrasonically cleaned with deionized water and dried naturally to obtain a pretreated titanium substrate.
[0088] (2) Prepare the active layer catalyst solution by mixing RuCl 3 、Ti(OC 4 H 9 ) 4 Dissolved in isopropanol and hydrochloric acid, where the concentration of Ru is 0.03 mol / L, the concentration of Ti is 0.05 mol / L, and the hydrochloric acid is 0.3 mol / L.
[0089] (3) The active layer catalyst solution was evenly coated on the pretreated titanium substrate, dried under an infrared lamp, and then moved to a muffle furnace for thermal oxidation treatment for 15 minutes at a thermal oxidation temperature of 470° C. The above steps were repeated 5 times;
[0090] (4) After the last drying, the sample was kept in a muffle furnace for 1 hour at a temperature of 470°C, and then taken out and naturally cooled to room temperature to obtain a mixed coating chlorine evolution anode. Sample number is #10.
[0091] Comparative Example 2
[0092] The chlorine-evolving anode was prepared according to the method of Comparative Example 1, except that the solvents used in step (2) were isopropanol and n-butanol, and the volume ratio of isopropanol to n-butanol was 1:1. The sample number was #11.
[0093] Figure 2 The voltage-time curves of the chlorine anode enhancement life test of Example 5 and Comparative Example 2 are as follows: Figure 2 It can be seen that the life of comparative example 2 is only 3 hours, while the life of example 5 is more than 1000 hours.
[0094] Comparative Example 3
[0095] The chlorine evolution anode was prepared according to the method of Comparative Example 1, except that the concentration of Ru in the active layer catalyst solution in step (2) was 0.01 mol / L. The sample number was #12.
[0096] Comparative Example 4
[0097] The chlorine evolution anode was prepared according to the method of Comparative Example 1, except that the concentration of Ru in the active layer catalyst solution in step (2) was 0.05 mol / L. The sample number was #13.
[0098] Comparative Example 5
[0099] The chlorine-evolving anode was prepared according to the method of Comparative Example 1, except that: in step (2), RuCl 3 SnCl 4 As active layer catalyst, the concentration of Ru is 0.03 mol / L, and the concentration of Sn is 0.05 mol / L. The sample number is #14.
[0100] Comparative Example 6
[0101] The chlorine anode was prepared according to the method of Comparative Example 1, except that: H was added in step (2). 2 Ir 6 6H 2 O、NbCl 5 As active layer catalyst, the concentration of Ir is 0.01 mol / L, and the concentration of Nb is 0.010 mol / L. The sample number is #15.
[0102] Comparative Example 7
[0103] A titanium mesh sheet of 10 cm × 10 cm size was sandblasted with corundum and the residue was cleaned with a compressed air jet. The sheet was then degreased in an ultrasonic bath using acetone for about 10 minutes. After drying, the sheet was immersed in a solution containing 250 g / L NaOH and 50 g / L KNO at about 100 °C. 3 After the alkaline treatment, the sheet was rinsed three times in deionized water at 60°C, changing the liquid each time. A small amount of HCl (about 1 mL per liter of solution) was added for the final rinse. The sheet was then air-dried and, due to the thin TiO x The film grew and a brown hue appearance was observed. A first hydroalcoholic solution of 100 mL was prepared, which contained RuCl in a mixture of water and 2-propanol acidified with HCl. 3 ·3H 2 O, H 2 IrCl 6 6H 2 O、TiCl 3 , having a molar composition of 30% Ru, 20% Ir and 50% Ti calculated as metals. Simultaneously, 100 mL of a second hydroalcoholic solution was prepared, comprising RuCl in a mixture of water and ethanol acidified with HCl. 3 ·3H 2 O, H 2 IrCl 6 6H2 O、NbCl 5 , PdCl 2 and tin chloride glycolate obtained according to the procedure disclosed in Example 3 of WO2005 / 014885, having a molar composition of 20% Ru, 10% Ir, 10% Pd, 59% Sn, 1% Nb, calculated as metals. The first solution is applied to the titanium mesh sheet by brushing in three coats; after each coat, drying is carried out at 100-110°C for about 10 minutes, followed by heat treatment at 450°C for 15 minutes. Each time before applying the subsequent coat, the sheet is cooled in air. The second solution is then applied to the titanium mesh by brushing in three coats, dried and finally heat treated, as with the first solution. At the end of the entire process, 9 g / m 2 is obtained, expressed as the sum of Ru, Ir and Pd calculated as metals. 2 Total precious metal loading of . Sample number is #16.
[0104] Comparative Example 8
[0105] A commercially available titanium plate (5 cm in length, 1 cm in width, and 1 mm in thickness) was immersed in a 10% oxalic acid solution at 90°C for 60 minutes for etching, then washed with water and dried. 4 H 9 RuCl was added to a 1% tantalum / ruthenium (OH) solution so that the molar ratio of ruthenium to tantalum was 90:10 and the total amount of ruthenium and tantalum was 50 g / L in terms of metal. 3 ·3H 2 O and TaCl 5 , prepare the coating liquid. The coating liquid was applied to the dried titanium plate, dried at 120°C for 10 minutes, and then thermally decomposed in an electric furnace maintained at 260°C for 20 minutes. The coating, drying, and thermal decomposition were repeated a total of 5 times to produce a chlorine anode having a catalyst layer formed on a titanium plate as a conductive substrate. The sample number is #17.
[0106] Strengthening life test of chlorine evolution anode:
[0107] A two-electrode system with a DC power supply was used, with the prepared sample as the working electrode and the titanium plate as the counter electrode. 2 SO 4 The solution is an electrolyte solution, and the current density is controlled at 2A / cm under constant current conditions. 2 , the starting voltage is increased by 10V and the test is stopped. The time at this moment is recorded. The cumulative time from the initial reaction to the stop of the test is calculated as the enhanced life test result of the sample. The test results correspond to Table 1.
[0108] Table 1. Enhanced life of anodes of Examples 1-9 and Comparative Examples 1-8
[0109] Sample No. Strengthening life (h) #1 860 #2 436 #3 696 #4 723 #5 >1000 #6 527 #7 881 #8 706 #9 621 #10 4 #11 3 #12 4.5 #13 4 #14 6 #15 102 #16 69 #17 9
[0110] It can be seen from Table 1 that the chlorine evolution anode of the present invention has an excellent enhanced life (or electrode service life), and the chlorine evolution anode still has excellent stability after long-term operation.
Claims
1. A chlorine evolution anode, characterized in that: It comprises a substrate, the surface of which is coated with an intermediate layer catalytic composition and an active layer catalytic composition in sequence; The intermediate layer catalytic composition comprises one or both of iridium oxide and ruthenium oxide and at least one oxide of a valve metal; The active layer catalytic composition comprises one or more of ruthenium oxide, iridium oxide and at least one valve metal oxide.
2. The anode according to claim 1, characterized in that The valve metal in the intermediate layer catalytic composition is different from the valve metal in the active layer catalytic composition.
3. The anode according to claim 1, characterized in that The valve metal is selected from at least one of tantalum, titanium, niobium, tin and antimony. Preferably, in the intermediate layer catalytic composition, the valve metal is selected from at least one of tantalum, titanium and niobium. Preferably, in the active layer catalytic composition, the valve metal is selected from at least one of titanium, tin and antimony.
4. The anode according to claim 1, characterized in that The intermediate layer catalytic composition is coated on the substrate surface in the form of a solution, that is, the intermediate layer catalytic composition solution is coated on the substrate surface. Preferably, the solvent used in the intermediate layer catalyst composition solution is at least one of isopropanol and n-butanol; for example, a mixture of isopropanol and n-butanol. Preferably, the volume ratio of isopropanol to n-butanol is 0.1 to 10:
1. Preferably, the preparation method of the intermediate layer catalytic composition solution is: The intermediate layer catalyst composition solution is obtained by mixing one or two of hexahydrate chloroiridic acid (H2IrCl6·6H2O), ruthenium trichloride (RuCl3) and a compound containing a valve metal. Preferably, in the preparation of the intermediate layer catalyst composition solution, the valve metal-containing compound is selected from one or more of tantalum pentachloride, tetrabutyl titanate, and niobium pentachloride.
5. The anode according to claim 4, characterized in that The concentration of iridium and / or ruthenium in the intermediate layer catalyst composition solution is 0.01-0.3 mol / L. Preferably, the concentration of the valve metal in the intermediate layer catalyst composition solution is 0.01-0.1 mol / L.
6. The anode according to claim 1, characterized in that The active layer catalytic composition is coated on the surface of the middle layer in the form of a solution, that is, the active layer catalytic composition solution is coated on the surface of the middle layer. Preferably, the solvent used in the active layer catalyst composition solution is at least one of isopropanol and n-butanol; for example, a mixture of isopropanol and n-butanol. Preferably, the volume ratio of isopropanol to n-butanol is 0.1 to 10:
1.
7. The anode according to claim 6, characterized in that The preparation method of the active layer catalytic composition solution is as follows: One or more of hexahydrate chloroiridic acid (H2IrCl6·6H2O), ruthenium trichloride (RuCl3), a valve metal-containing compound, and hydrochloric acid are mixed to obtain the active layer catalyst composition solution. Preferably, in the preparation of the active layer catalyst composition solution, the valve metal-containing compound is selected from one or more of tetrabutyl titanate, tin tetrachloride, and antimony trichloride. Preferably, the concentration of iridium and / or ruthenium in the active layer catalyst composition solution is 0.01 mol / L to 0.3 mol / L; Preferably, the concentration of the valve metal in the active layer catalyst composition solution is 0.01 mol / L to 0.4 mol / L; Preferably, the content of hydrochloric acid in the active layer catalyst composition solution is 0.015 mL HCl / mL~0.025mL HCl / mL.
8. The method for preparing the anode according to any one of claims 1 to 7, characterized in that: The method comprises: (S1) coating the intermediate layer catalytic composition on a substrate, heating and heat treating the substrate to obtain a substrate containing the intermediate layer; (S2) coating the active layer catalytic composition on the intermediate layer of step (S1), heating and heat treatment, to obtain a substrate containing the active layer and the intermediate layer in sequence; (S3) heat-treating the substrate containing the active layer and the intermediate layer in step (S2) to obtain the chlorine evolution anode.
9. The method according to claim 8, characterized in that In step (S1), the atmosphere of the heat treatment is an oxygen-containing atmosphere. Preferably, in step (S1), the heat treatment temperature is 450-550° C., and the heat treatment time is 10-20 min. Preferably, in step (S2), the atmosphere of the heat treatment is an oxygen-containing atmosphere; In step (S2), the heat treatment temperature is 450-550° C., and the heat treatment time is 10-20 min. Preferably, in step (S3), the atmosphere of the heat treatment is an oxygen-containing atmosphere; In step (S3), the heat treatment temperature is 450-550°C, and the heat treatment time is 30-60 minutes.
10. Use of the anode according to any one of claims 1 to 7 in the chlor-alkali industry.
Citation Information
Patent Citations
Electrode for electrochemical processes and method for producing the same
WO2005014885A1